2006
DOI: 10.1088/0264-9381/23/7/008
|View full text |Cite
|
Sign up to set email alerts
|

On the quantum origin of the seeds of cosmic structure

Abstract: The current understanding of the quantum origin of cosmic structure is discussed critically. We point out that in the existing treatments a transition from a symmetric quantum state to an (essentially classical) non-symmetric state is implicitly assumed, but not specified or analyzed in any detail. In facing the issue we are led to conclude that new physics is required to explain the apparent predictive power of the usual schemes. Furthermore we show that the novel way of looking at the relevant issues opens n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
481
2
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(493 citation statements)
references
References 45 publications
6
481
2
4
Order By: Relevance
“…To complete the specification of the effective theory, we incorporate supersymmetry breaking by an anti-D3-brane in a warped throat region, which leads to a term in the potential of the form 199) with a constant that depends on the warp factor at the location of the anti-D3-brane. 67 The authors of [618] showed that for suitable values of the parameters W 0 , A, B, a, b, , the potential for T develops a saddle point 68 that is suitable for inflation. The evolution is primarily in the direction of the axion Im(T ), but Re(T ), corresponding to the compactification volume, does also evolve.…”
Section: Racetrack Inflationmentioning
confidence: 99%
“…To complete the specification of the effective theory, we incorporate supersymmetry breaking by an anti-D3-brane in a warped throat region, which leads to a term in the potential of the form 199) with a constant that depends on the warp factor at the location of the anti-D3-brane. 67 The authors of [618] showed that for suitable values of the parameters W 0 , A, B, a, b, , the potential for T develops a saddle point 68 that is suitable for inflation. The evolution is primarily in the direction of the axion Im(T ), but Re(T ), corresponding to the compactification volume, does also evolve.…”
Section: Racetrack Inflationmentioning
confidence: 99%
“…It has been argued that in those circumstances the smeared inflaton field behaves as a classical stochastic process. (This is closely related to the quantum to classical transition problem for the inflaton fluctuations [18,19,20,21,22,23,24,25].) If that is the case, one can use a particular realization of the smeared inflaton right before the last 60 e-folds of inflation as the classical background configuration φ(η) and treat it in the same way in which one would have dealt with a quantum expectation value.…”
Section: B Einstein-langevin Equation For Cosmological Perturbationsmentioning
confidence: 99%
“…Moreover, the recent detection of gravity waves by LIGO [4] removes all lingering doubts about the reality of such waves (if there were any remaining, given the dramatic indirect evidence provided by the Binary Pulsar studies [5]). This only increases the urgency to resolve the tension generated by the predictions regarding B-modes and our failure to detect them.As initially argued in [6], the standard inflationary account for the emergence of the primordial perturbations lacks a crucial element capable of accounting for the transition from the initially homogeneous and isotropic quantum state into a state lacking such symmetries. The objective of this letter is to show that the adoption of a framework that explicitly introduces this element drastically modifies the predictions for the shape and amplitude of the primordial gravity waves (without also altering confirmed predictions of inflation) [7].…”
mentioning
confidence: 99%
“…As initially argued in [6], the standard inflationary account for the emergence of the primordial perturbations lacks a crucial element capable of accounting for the transition from the initially homogeneous and isotropic quantum state into a state lacking such symmetries. The objective of this letter is to show that the adoption of a framework that explicitly introduces this element drastically modifies the predictions for the shape and amplitude of the primordial gravity waves (without also altering confirmed predictions of inflation) [7].…”
mentioning
confidence: 99%